Why victimology should stay positive: The ongoing need for positive victimology - Ronel Natti (Temida)
This paper presents the need for positive victimology and its unique contribution to victimology. Victimology presented a shift in attention and awareness in practice, research and theory, by focusing on victims of crime and of abuse of power, and on victims’ rights and victims’ services. Positive victimology indicates a more specified shift in attention and awareness, within the larger shift of victimology. This shift stands in line with positive psychology, positive criminology and the idea of victims’ victimology. It denotes an approach to provide the following, as much as possible: 1. A wide range of social responses to the victims and their victimization that victims can experience as positive, 2. Positive outcomes of healing and recovery for victims, and 3. Positive integration of victims. Within each of those, positive victimology suggests a pragmatic coordinated system that ranges from definitions of negative poles to those of positive ones. When moving towards the positive pole at any given coordinate, a sense of justice is an important factor that might reduce the impact of the harm. Support is also a crucial factor and at the very positive pole, stands human, inter-personal love.